2012
DOI: 10.1111/j.1439-0507.2012.02209.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of dermatophytosis in junior combat and non‐combat sports participants

Abstract: Participation in competitive sports is popular and widely encouraged worldwide. Herein, we investigated 252 male and 67 female sports players, aged 16.4 ± 1.3 years, active in 15 different types of combat (n = 143) and non-combat (n = 176) sports. Of the 319 participants in this study, 11 (3.5%) players, including six wrestlers, four football players and one handball player, all of whom were men, harboured dermatophytic fungi. Briefly, Trichophyton tonsurans was present in three athletes, who were scalp carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…A number of studies have shown that T. tonsurans is widely distributed in contact sports, particularly martial arts 19,26,29–33 . However, in this study only 4 of 23 patients practiced martial arts and only 1 person practiced another contact sport.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…A number of studies have shown that T. tonsurans is widely distributed in contact sports, particularly martial arts 19,26,29–33 . However, in this study only 4 of 23 patients practiced martial arts and only 1 person practiced another contact sport.…”
Section: Discussionmentioning
confidence: 53%
“…A number of studies have shown that T. tonsurans is widely distributed in contact sports, particularly martial arts. 19,26,[29][30][31][32][33] However, in this study only 4 of 23 patients practiced martial arts and only 1 person practiced another contact sport. The data therefore highlight that T. tonsurans is not limited to outbreaks in contact sports but more widely distributed in the general population.…”
Section: Ta B L Ementioning
confidence: 99%
“…The examined mats were different from the traditional thick and rough fabric (esparto, palm, or reed) mats [ 11 ] that retain fungal spores. These mats are frequently used in countries, such as Turkey [ 6 , 9 , 15 ] and Iran [ 2 , 13 - 16 ]. In a previous study, skin-to-skin contact was proposed as the most likely mode of transmission since the isolation of the fungus from the mats was not possible; accordingly, they recommended periodic check-ups as necessary measures [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, asymptomatic carriers have been also reported [ 5 ]. This disease is commonly observed worldwide [ 8 , 9 ]; however, in Mexico, the disease could be underreported since there are no previous reports of tinea gladiatorum. Herein, we present the first outbreak of this infection among high school wrestlers in Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…This fungus has most frequently been seen in the Indian subcontinent, where it has been isolated from the soil as well as from infected animals and humans. For some years, the preponderance of known isolates was from monkeys, as implied by the epithet ‘simii ,’ but in time, a regular association with poultry and poultry farm work was also noticed [ 5 , 8 , 9 ]. With isolates from disparate sources like soil in the Ivory Coast [ 5 ] and cattle in southern India [ 10 ] the species has formed a pattern most consistent with geophilic ecological classification, i.e., breaking down hair, feathers and other keratinous remains in contact with soil, but it cannot be ruled out as a possible zoophile connected with soil-dwelling animals.…”
Section: Discussionmentioning
confidence: 99%